2006
DOI: 10.1890/0012-9658(2006)87[2882:ltgfat]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Larval Tolerance, Gene Flow, and the Northern Geographic Range Limit of Fiddler Crabs

Abstract: Despite growing interest in species' range shifts, little is known about the ecological and evolutionary factors that control geographic range boundaries. We investigated the processes that maintain the northern range limit of the mud fiddler crab (Uca pugnax) at North Scituate, Massachusetts, USA (42 degrees 14' N), located approximately 60 km north of Cape Cod. Larvae from five populations in Massachusetts were reared under controlled temperatures to test whether cooler water near the edge of this species' r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(129 citation statements)
references
References 58 publications
5
122
2
Order By: Relevance
“…Mortality associated with an increase in duration of development at low temperatures and the latitudinal temperature diminution could limit the larval dispersal of this species, and consequently its northern distribution. also, the northern limit of Uca pugnax in the northwestern atlantic is likely maintained by the influence of cooler water temperatures on the larval phase, as reported by Sanford et al (2006), who found that there are suitable northern habitats for this species (extensive salt marshes) and that transplanted adult crabs could resist severe winter conditions. However, few larvae completed development at temperatures that they would regularly encounter north of their range boundary.…”
Section: Larval Morphology and Uca Phylogenysupporting
confidence: 53%
“…Mortality associated with an increase in duration of development at low temperatures and the latitudinal temperature diminution could limit the larval dispersal of this species, and consequently its northern distribution. also, the northern limit of Uca pugnax in the northwestern atlantic is likely maintained by the influence of cooler water temperatures on the larval phase, as reported by Sanford et al (2006), who found that there are suitable northern habitats for this species (extensive salt marshes) and that transplanted adult crabs could resist severe winter conditions. However, few larvae completed development at temperatures that they would regularly encounter north of their range boundary.…”
Section: Larval Morphology and Uca Phylogenysupporting
confidence: 53%
“…Comparative and integrated analysis of ecological transitions (Connolly et al 2001, Navarrete et al 2008, changes in behavior associated with these transitions (Sanford et al 2003), genetic patterns concordant with these transitions (Petersen 2007), and experimental evaluation of fitness (Sanford et al 2006) at all life stages of coastal invertebrates will ultimately provide significant insights into the function of coastal communities and the diversity they harbor. Currents and their effect on dispersal are clearly responsible for some of these observed patterns, but the environmental changes in climate and topographic conditions, which usually modulate the changes in coastal hydrography, might exert unsuspected and poorly studied selective pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Mar Ecol Prog Ser 412: [141][142][143][144][145][146][147][148][149][150] 2010 although these supply-side processes are often highly variable in space and time (see Underwood & Fairweather 1989, Caley et al 1996, Hunt & Scheibling 1997, they sometimes reflect latitudinal gradients of temperature, currents, wave exposure and nutrient availability in the ocean (Connolly & Roughgarden 1998, Connolly et al 2001, Zacherl et al 2003, Sanford et al 2006. Consequently, the geographic distribution of benthic marine invertebrates, particularly as a species approaches its range limit, may be strongly influenced by latitudinal gradients in the supply and early life history of larvae.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%